Chordate betagamma-crystallins and the evolutionary developmental biology of the vertebrate lens. - Riyahi, K; Shimeld, S (2007)
Several animal lineages, including the vertebrates, have evolved sophisticated eyes with lenses that refract light to generate an image. The nearest invertebrate relatives of the vertebrates, such as the ascidians (sea squirts) and amphioxus, have only basic light detecting organs, leading to the widely-held view that the vertebrate lens is an innovation that evolved in early vertebrates. From an embryological perspective the lens is different from the rest of the eye, in that the eye is primarily of neural origin while the lens derives from a non-neural ectodermal placode which invaginates into the developing eye. How such an organ could have evolved has attracted much speculation. Recently, however, molecular developmental studies of sea squirts have started to suggest a possible evolutionary origin for the lens. First, studies of the Pax, Six, Eya and other gene families have indicated that sea squirts have areas of non-neural ectoderm homologous to placodes, suggesting an origin for the embryological characteristics of the lens. Second, the evolution and regulation of the betagamma-crystallins has been studied. These form one of the key crystallin gene families responsible for the transparency of the lens, and regulatory conservation between the betagamma-crystallin gene in the sea squirt Ciona intestinalis and the vertebrate visual system has been experimentally demonstrated. These data, together with knowledge of the morphological, physiological and gene expression similarities between the C. intestinalis ocellus and vertebrate retina, have led us to propose a hypothesis for the evolution of the vertebrate lens and integrated vertebrate eye via the co-option and combination of ancient gene regulatory networks; one controlling morphogenetic aspects of lens development and one controlling the expression of a gene family responsible for the biophysical properties of the lens, with the components of the retina having evolved from an ancestral photoreceptive organ derived from the anterior central nervous system.